2019
DOI: 10.1124/dmd.118.085241
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Evaluation of the Complex Drug-Drug Interactions of Maraviroc: Contribution of Cytochrome P450 3A, P-Glycoprotein and Organic Anion Transporting Polypeptide 1B1

Abstract: The aim of the present study was to quantitatively evaluate the drugdrug interactions (DDIs) of maraviroc (MVC) with various perpetrator drugs, including telaprevir (TVR), using an in vitro data-informed physiologically based pharmacokinetic (PBPK) model. MVC showed significant active uptake and biliary excretion in sandwich-cultured human hepatocytes, and biphasic organic anion transporting polypeptide (OATP)1B1-mediated uptake kinetics in transfected cells (high-affinity K m ∼5 mM). No measureable active upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 61 publications
(73 reference statements)
2
19
0
Order By: Relevance
“…A single oral dose of ketoconazole increased the plasma concentrations of nifedipine and omeprazole. Based on the inhibitory effect of ketoconazole on CYP3a [ 72 ], a decreased dehydronifedipine formation and an increased nifedipine concentration in rat plasma could be expected, which was consistent with previous reports [ 17 , 18 ]. In case of omeprazole, CYP3A and CYP2C19 are involved in the omeprazole metabolism resulting in the formation of omeprazole sulfone and 5-hydroxyomeprazole, respectively [ 56 ].…”
Section: Discussionsupporting
confidence: 91%
“…A single oral dose of ketoconazole increased the plasma concentrations of nifedipine and omeprazole. Based on the inhibitory effect of ketoconazole on CYP3a [ 72 ], a decreased dehydronifedipine formation and an increased nifedipine concentration in rat plasma could be expected, which was consistent with previous reports [ 17 , 18 ]. In case of omeprazole, CYP3A and CYP2C19 are involved in the omeprazole metabolism resulting in the formation of omeprazole sulfone and 5-hydroxyomeprazole, respectively [ 56 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several studies have demonstrated that the activities of CYP3A, P-gp, and selected OATPs in the intestine and/or liver may be involved in food/beverage–drug interactions [ 8 , 9 , 10 ]. In the intestine and liver, GT extract or EGCG may inhibit both CYP3A activity and P-gp, resulting in increasing intestinal drug absorption and plasma drug concentrations [ 16 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has suggested that modulations of the activities of CYP3A, P-gp, and OATPs in the intestine or liver may be involved in food/beverage–drug interactions [ 8 , 9 , 10 ]. Studies have indicated that the inhibition of CYP3A or P-gp in the intestine or liver by the consumption of grapefruit juice increases the bioavailability of several orally administered drugs, including lovastatin, simvastatin, and atorvastatin [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maraviroc is reported to be a substrate of organic anion transporting polypeptide (OATP)1B1 with its K m value of 5 mM. 20 After administration of the maraviroc in a Phase 1 study, the C max, bood, u were approximately 1.4 mM even at 1200 mg. In addition, the maximal concentration of unbound maraviroc at the hepatic inlet (C max,in,u ) at 100 and 1200 mg were calculated to be 5.6 and 67.4 mM, respectively.…”
Section: Discussionmentioning
confidence: 99%